Scalar Field Modes in de Sitter Spacetime with Negative Curvature Spatial Foliation - Saharian, A. A.; Petrosyan, T. A.; Chitchyan, S. S.; Grigoryan, A. Kh.
The mode functions for a massive scalar field with general curvature parameter are determined in background of -dimensional de Sitter spacetime with neagtive curvature spatial foliation. The general case of a maximally symmetric vacuum state is considered. It is shown that the adiabatic and conformal vacua coincide and the corresponding mode functions are specified. Limiting cases are discussed including the flat spacetime limit. The latter corresponds to the Milne universe. For a conformally coupled massless field the problem under consideration is conformally related to the one in static spacetime with a constant negative curvature space. It is shown that in this special case the modes are reduced to those previously discussed in the literature. The mode sum for the positive-frequency Wightman function is constructed.
Keywords: Physics; Quantum mechanics